New developments in high speed machining - Sudhakar, Mal; Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2003)
A presentation regarding the new development and new technologies in high speed machining industries
Code no : DV03PUB71
Recorded at the High Speed Machining Technical Conference, Apr. 8 & 9, 2003, Itasca, Ill.
Title from title screen
Presenter: Mal Sudhakar
Keywords: High-speed machining; Machining